LINGUISTIC CHARACTERISTICS OF THE TERMS RELATED TO THE “MARKET ECONOMY” CONCEPT WITHIN BUSINESS ENGLISH LEXICON - Urinova Urazgul Boykobilovna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Annotation. The importance of learning English language is becoming more attractive theme day by day in Uzbekistan and it means the cross-cultural relationships are developing in our country. The thing makes us happy the evaluation of the language observed in all fields, as well as in world literature. Nowadays Uzbek students have opportunity to read the masterpieces of any kind of foreign literature in English. 1 Learning foreign languages is very important in our country nowadays. As the first president of Uzbekistan, Islam Karimov said: “The education of the population in the process of the assimilation of ‘world democratic values is of primary importance”. 2 The following article is devoted to the study of Analyses of linguistics characteristics of the terms related to the "market economy " concept within Business English Lexicon.